Renewable energy transition and climate finance nexus in sub-Saharan Africa - Anthony Amoah; Benjamin Amoah; Edmund Kwablah; Rexford Kweku Asiama (Global Environmental Change Advances)
Developing countries in sub-Saharan Africa (SSA), which are key recipients of climate finance aimed at supporting transitions to cleaner energy, have experienced a general decline in renewable energy transitions despite ongoing financial support. This study employs secondary panel data from 36 SSA countries covering the period 2000 to 2022 and uses a Generalised Method of Moments (GMM) Panel Vector Autoregressive (PVAR) regression model to explore the relationship between climate finance and renewable energy transitions in the region. The findings suggest that evidence of prior transitions to renewable energy positively influence the availability of current climate finance. This suggests that increases in climate finance are responsive to renewable energy transitions in SSA countries. From a policy perspective, this study underscores the importance of SSA countries strategically advancing toward a zero-carbon economy to attract greater climate-related investments and foster a sustainable future.